1937
DOI: 10.1039/jr9370001252
|View full text |Cite
|
Sign up to set email alerts
|

257. Reaction kinetics and the Walden inversion. Part VI. Relation of steric orientation to mechanism in substitutions involving halogen atoms and simple or substituted hydroxyl groups

Abstract: The known relationships between the mechanism of aliphatic substitution and the structures of the compounds substituted form a starting point for the investigation of the laws governing the steric orientation of substitution. As a result of work reported in the preceding papers, certain general principles relating to the orientation of substitution are advanced. Detailed discussion is confined to the reciprocal replacements of *Hal and -OR, and within this field previously recorded stereochemical observations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
0
2

Year Published

1954
1954
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(73 citation statements)
references
References 1 publication
(5 reference statements)
2
69
0
2
Order By: Relevance
“…1 As an alternative possibility, the "internal return-like" mechanism, so called S N ilike mechanism has been suggested, depicting the nucleophilic attack from the same face as the leaving group departure. 1,10,15 The concept of a general internal nucleophilic substitution mechanism S N i (Substitution Nucleophilic internal) that is neither simple S N 1 nor S N 2 was first invoked to explain unusual stereochemical outcomes of simple alkyl halides; 16 this so-called Ingold-type nomenclature focuses on defining transformation type. This mechanism is classically invoked in the characterization of the reactive stereochemical course of secondary alkyl chlorosulfites which leads to retention when the nucleophile and leaving group are constrained on the same face; importantly these early studies highlighted that when constraint was removed then attack occurred from the other face.…”
Section: Introductionmentioning
confidence: 99%
“…1 As an alternative possibility, the "internal return-like" mechanism, so called S N ilike mechanism has been suggested, depicting the nucleophilic attack from the same face as the leaving group departure. 1,10,15 The concept of a general internal nucleophilic substitution mechanism S N i (Substitution Nucleophilic internal) that is neither simple S N 1 nor S N 2 was first invoked to explain unusual stereochemical outcomes of simple alkyl halides; 16 this so-called Ingold-type nomenclature focuses on defining transformation type. This mechanism is classically invoked in the characterization of the reactive stereochemical course of secondary alkyl chlorosulfites which leads to retention when the nucleophile and leaving group are constrained on the same face; importantly these early studies highlighted that when constraint was removed then attack occurred from the other face.…”
Section: Introductionmentioning
confidence: 99%
“…在过去的几十年中, 关于亲核取代反应的机理研究已经相当地成熟. 尤其是 当亲核取代反应发生在一个饱和的原子上, 比如 sp 3 -C (sp 3 杂化的碳原子), S N 1( 单分子亲核取代反应) [2] 和 S N 2(双分子亲核取代反应) [3] 这两种反应机理是最常见 的两类. 对于不饱和碳原子, 例如 sp 这意味着 sp 2 -C-Cl 键中氯原子的离去能力相对要小(图 1) [5] .…”
Section: 亲核取代反应unclassified
“…DISCUSSION A study of the chemical properties of 1-(P-chloroethy1)-2-imidazolidone (111), 1-(Paminoethy1)-3-nitro-2-imidazolidone hydrochloride (V), and 1-(p-nitraminoethy1)-2-imidazolidone (VI) obtained (2) from the reaction of thionyl chloride with 1-(p-hydroxyethyl)-2-nitriminoimidazolidine has indicated that the origin of these products may be represented as shown in Chart I. The mechanism for the chlorination of 1-(0-hydroxyethyl)-2-nitriminoimidazolidine (I) to 1-(p-chloroethy1)-2-nitriminoimidazolidine (111) is assumed to be similar to that suggested (8) for the chloriilation of alcohols with thionyl chloride. …”
Section: Introductionmentioning
confidence: 99%